An Analysis Of Students’ Difficulties In Writing Recount Text At Tenth Grade At One Of Senior High School In Jambi - Sari, Lisa Novita; Mayasari, Ichlasul Baroqah Yuni Harnita; Fathuredha, Hafidzatunnur (Peneliti.net, 2024)
The purpose of this study was to determine the types of student difficulties and the factor that made the students had difficulties in writing recount text in class X C MAN AL-Hidayah Jambi. This research is a qualitative descriptive study where the data was taken from the analysis of students' recount text writing and interviews. Methods of data collection were observation, documentation and interviews. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of this study indicate that students have difficulties in content, organization, language, vocabulary and mechanics in writing recount text.